PPM of labeled fluorine and analyzed fluorine in pediatric toothpaste commercialized in Lima-Peru. - Córdova-López, Ofelia (2019)
Objective: To determine the concentration of fluorine ppm in toothpastes for children that are commercialized in Lima Peru in the year 2017. Material y Methods: It is an observational, descriptive, cross-sectional study. 48 pediatric toothpastes sold in pharmaceutical establishments (pharmacies and drugstores) in Lima were collected. The Student t and Wilcoxon t tests were used for a single sample. Results: The diﬀerence between the concen-tration of fluorine as labeled and found in Colgate of 1 100 ppm was -119.8 ppm (median), Oral B of 500 ppm was -57.05 ppm (median). The diﬀerence between the concentration of fluorine according to labeling and that found based on the average was Colgate of 500 ppm: -34.2 ppm, Farmadent of 452 ppm: -36.27 ppm, Dentito of 550 ppm: -520.1 ppm, Aqua fresh of 500 ppm: +41.67 ppm, Vitis of 1 000 ppm: +141.85 ppm, Aqua Fresh of 1 150 ppm: +112.82 ppm; among those mentioned only Aqua Fresh 500 ppm was not significant. With respect to the pH of toothpastes, the averages were 5.92; 5.5; 5.5; 6; 6; 5.5; 5.5; 6, respectively. Conclusions: Five types of toothpaste have lower concentrations than labeling and three types of toothpastes have concentrations higher than the labeling (of which one was not significant).